2007
DOI: 10.1111/j.1432-2277.2007.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, depression and quality of life in patients on a renal transplantation waiting list

Abstract: Summary To study nonadherence, and its relationship with depression and quality of life (QOL) in patients on a cadaveric renal transplantation waiting list (RTWL). In 86 RTWL patients (56 men/30 women), there were 49 nonadherent patients (age, 46.8 ± 21.8 years) and 37 adherent patients (age, 42.8 ± 12.1 years). Clinical nonadherence was defined as skipping or shortening dialysis sessions, interdialytic weight gain (IDWG) of >5.7% body weight, a predialysis potassium level of >6 mEq/l and a predialysis phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 21 publications
2
48
2
1
Order By: Relevance
“…In addition to this, quantitative research has shown that those on the waiting list for a kidney from a deceased donor are more prone to depression and anxiety than those due to receive from a living donor (Akman et al, 2007). As such, these findings 4 strengthen the argument that this group is worthy of further exploration.…”
Section: Introductionmentioning
confidence: 77%
“…In addition to this, quantitative research has shown that those on the waiting list for a kidney from a deceased donor are more prone to depression and anxiety than those due to receive from a living donor (Akman et al, 2007). As such, these findings 4 strengthen the argument that this group is worthy of further exploration.…”
Section: Introductionmentioning
confidence: 77%
“…A recent quantitative review reported that depressed patients with a chronic illness are about threefold noncompliant to medical treatment than non-depressed patients [27]. Similarly, depressive disorder in dialysis was associated with double risk of no compliance to calcium-phosphorus dietary prescriptions [26]. According to this, the patient's perception of adherence to dietary restriction can be undermined by decreased cognitive functions, reduced concentration abilities, no care about prescribed therapies and negative thoughts about self [28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be possibly related to patient's poor compliance to therapy induced by depressive feelings. In fact, depression could be responsible for non-adherence with treatment through behavioural pathways [26]. A recent quantitative review reported that depressed patients with a chronic illness are about threefold noncompliant to medical treatment than non-depressed patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of HD patients generally focus on those awaiting for it. [8][9][10][11][12][13][14][15] . The medical reasons for not being eligible to transplant mainly involve critical organ function (advanced heart failure, liver cirrhosis, obstructive pulmonary disease, visceral malignancies, and coronariopathy).…”
Section: Introductionmentioning
confidence: 99%